ANTIOXIDANT ACTIVITY OF Homotrigona fimbriata PROPOLIS EXTRACT - Rabiatul Demiati; Rendri Arista Avimaro; Paula Mariana Kustiawan (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Antioxidant compounds have a role in protecting the body from free radicals, Propolis from Homotrigona fimbriata species is widely used as an alternative to natural healing in East Kalimantan. The secondary metabolite compounds in propolis contain many flavonoids and phenolic compounds. These compounds can be utilized to fight free radicals. The purpose of this study was to determine the antioxidant content of stingless bee (Homotrigona fimbriata) propolis extract. This was a quantitative study of the antioxidant potential of propolis extract. The benchmark antioxidant activity was measured based on its ability to counteract free radicals using the DPPH method. The results of this study showed the presence of secondary metabolites of alkaloids, flavonoids, tannins, and saponins as well as antioxidant activity of Homotrigona fimbriata propolis extract with a value of 95,8 ppm as strong category. This can be caused by differences in geographical location, and various resins found in the trees around the beehive will affect antioxidant activity. Keywords: Homotrigona fimbriata, antioxidant, stingless bee